Prevalence of low back pain in adolescent athletes - an epidemiological investigation - Schmidt, C. P.; Zwingenberger, S.; Walther, A.; Reuter, U.; Kasten, P.; Seifert, J.; Günther, K. P.; Stiehler, M. (International Journal of Sports Medicine, 2014)
Low back pain (LBP) is a common symptom in the populations of western countries, and adolescent athletes seem to be prone to LBP. The main objective of this study was to analyze the point (LBP within the last 48 h), 1-year (LBP within the last 12 months) and lifetime (LBP within the entire life) prevalence rates of LBP in adolescent athletes participating in various sports. We also assessed the characteristics of LBP and its association with potential risk factors. To this end, 272 competitive adolescent athletes involved in 31 different sports (158 males, 113 females, 15.4±2.0 years, body mass index [BMI] 20.3±2.4 kg/m2) were enrolled in a 10-month prospective clinical trial that included a questionnaire and physical examination. We found a point prevalence of 14%, a 1-year prevalence of 57%, and a lifetime prevalence of 66% for LBP. The mean age of first appearance of LBP was 13.1±2.0 years. The lifetime prevalence was significantly higher in volleyball than in biathletes (74.3 vs. 45.7%, p=0.015). Our findings confirm that LBP is a common symptom in adolescent athletes; LBP prevalence correlates with sports participation and individual competitive level. Adolescent athletes with LBP should receive a thorough diagnostic work-up and adapt training and technique correspondingly when indicated.